2004
DOI: 10.1152/ajpheart.00153.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ascorbic acid on arterial hemodynamics during acute hyperglycemia

Abstract: Mortality increases when acute coronary syndromes are complicated by stress-induced hyperglycemia. Early pulse wave reflection can augment central aortic systolic blood pressure and increase left ventricular strain. Altered pulse wave reflection may contribute to the increase in cardiac risk during acute hyperglycemia. Chronic ascorbic acid (AA) supplementation has recently been shown to reduce pulse wave reflection in diabetes. We investigated the in vivo effects of acute hyperglycemia, with and without AA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 49 publications
4
29
1
Order By: Relevance
“…[27][28][29][30] The present findings extend these observations by demonstrating a tonic inhibitory effect of oxidative stress on carotid artery compliance in healthy estrogen-deficient postmenopausal women that is not observed in premenopausal females. Consistent with the present results in premenopausal females, our laboratory demonstrated recently that acute and chronic ascorbic acid administration have no effect on carotid artery compliance in healthy young males.…”
Section: Moreau Et Al Oxidative Stress and Arterial Stiffnesssupporting
confidence: 85%
“…[27][28][29][30] The present findings extend these observations by demonstrating a tonic inhibitory effect of oxidative stress on carotid artery compliance in healthy estrogen-deficient postmenopausal women that is not observed in premenopausal females. Consistent with the present results in premenopausal females, our laboratory demonstrated recently that acute and chronic ascorbic acid administration have no effect on carotid artery compliance in healthy young males.…”
Section: Moreau Et Al Oxidative Stress and Arterial Stiffnesssupporting
confidence: 85%
“…Previously, it has been shown that AIx is increased during hyperglycaemia in healthy men [11]. However, this result has not been confirmed by other studies.…”
mentioning
confidence: 68%
“…Indeed, hyperglycemia per se has been observed to negatively affect endothelium-dependent vasodilation in human arteries, 10 increase pulse wave reflections, and decrease aortic distensibility in healthy male volunteers. 29 Modest increases in postprandial glucose can acutely lower FMD in healthy subjects as well as those with impaired glucose tolerance and T2DM, though the latter groups show greater reductions. 7,8 Consistent with our results, the inverse association between FMD and plasma glucose found in these studies suggests a continuous relationship between increasing glucose concentrations and decreasing endothelial function.…”
Section: 2425mentioning
confidence: 98%